Effect of COVID-19 on dental care for children during the post-pandemic era in Ghana: a concern for policymaking - Agyekum, Benjamin Adu; Tuglo, Lawrence Sena (Frontiers in Dental Medicine, 2023)
The impacts of COVID‐19 have been sensed globally, especially in the delivery of healthcare services such as dental care, although the incidence in Africa is comparatively low. This review article aimed to explore the COVID-19 pandemic lockdown and its impact on dental care for children in Ghana. Some dental facilities in Ghana have been experiencing multiple challenges in service delivery, and the ongoing COVID-19 pandemic has aggravated the situation. The COVID-19 pandemic has interrupted all dental care in many parts of Ghana due to its impact on food insecurity, economic breakdown, depression, shortage of essential instrument supplies, inadequate health workers, and poor infection control practices, which present main risks to dental care. Furthermore, the shutting of dental departments due to the COVID-19 lockdown has restricted the accessibility and utilization of dental services, especially for children. Hence, to avoid further and future pandemics and their impacts on dental care, there is a need to address these implications identified and prepared for the delivery of suitable dental healthcare in Ghana.